2017
DOI: 10.1002/cb.1697
|View full text |Cite
|
Sign up to set email alerts
|

Price fairness, satisfaction, and trust as antecedents of purchase intentions towards organic food

Abstract: Health and environmental issues are increasingly important in consumers' decision‐making process. Accordingly, demand for organic food is rapidly growing. In this context, the objective of this study is to analyze the relationship between price fairness, satisfaction, trust, and purchase intentions towards organic food. With this aim, empirical data were collected with self‐administrated questionnaires from a convenience sample of consumers from Sakarya, Turkey. Proposed hypotheses were tested with structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
95
1
15

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 86 publications
18
95
1
15
Order By: Relevance
“…This study used SPSS 20.0 and AMOS 7.0 to test the reliability and validity of the questionnaire based on scales in prior studies (Kim et al, 2008;Cucchiara et al, 2015;Konuk, 2018). It measured consumers' attitude and purchase intention toward organic food using a 7-point Likert scale.…”
Section: Validity and Reliabilitymentioning
confidence: 99%
“…This study used SPSS 20.0 and AMOS 7.0 to test the reliability and validity of the questionnaire based on scales in prior studies (Kim et al, 2008;Cucchiara et al, 2015;Konuk, 2018). It measured consumers' attitude and purchase intention toward organic food using a 7-point Likert scale.…”
Section: Validity and Reliabilitymentioning
confidence: 99%
“…Our results show that those who perceived price unfairness after becoming aware of discounts on similar shows revealed decreased intention to purchase tickets at regular prices. Santos et al [51] and Konuk [10] found similar consumer behavior in marketing.…”
Section: Discussionmentioning
confidence: 80%
“…Negative perceptions of price fairness may result in reduced intention to purchase tickets at cover prices, as suggested by previous studies [7][8][9][10], that is to say, consumers may be less willing to purchase tickets at regular prices if the discount promotions for similar performing arts products create the perception that regular prices are unfair. Consumers who perceive price unfairness may spread negative word-of-mouth information in addition to resisting purchases, and therefore negatively affect the sustainable long-term profits of suppliers [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 84%
“…To measure value co-creation, all the items were adapted from Opata et al (2019). On consumers' co-creation outcomes, specifically customer satisfaction, four items that measure customers' satisfaction were adapted from Herrmann et al (2007) and Konuk (2018). The study adapted items from Herrmann et al (2007) and Konuk (2018) to measure price fairness.…”
Section: Methodsmentioning
confidence: 99%
“…However, not much research has been carried on the effect of price fairness perceptions on customer satisfaction in the perspective of value co-creation. Konuk (2018) opined in his article that price is an immediate antecedent to customer satisfaction. In the setting of this study, we used the definition of price fairness provided by Xia et al (2004).…”
Section: Price Fairness Perceptionmentioning
confidence: 99%